Simulation of Determining Outstanding Lecturers Using the Fuzzy Logic - Alwendi, Alwendi; Mandopa, Andi Saputa; Indra, Hamdi (Journal of Engineering Education and Pedagogy, 2023)
In the learning process, lecturers have quite an important role because a lecturer is required to manage or organize so that the learning process can run well. The objectives of writing this article are Determine the category of outstanding lecturers by applying fuzzy logic with the mamdani method. Produce a mathlab program developed using the mamdani method to determine outstanding lecturers at Graha Nusantara University. Today, information technology, especially soft computing technology, is developing very quickly. One of the most developed software computing technologies is fuzzy logic, as it can be used to measure various ambiguous, camouflaged or fuzzy phenomena. One of the research topics applying fuzzy logic is the evaluation system in the research field. Research conducted by professors from Graha Nusantara Padangsidimpuan University in Simlitabmas data Still in the category of orientation to move to intermediate level, professors from UGN Padangsidimpuan are challenged to be able to develop, contribute and apply knowledge required for research. To do this, we needed an application that could be used to calculate and record teacher performance in outcomes research. The purpose of this study is to apply fuzzy logic with Mamdani method to evaluate the research efficiency of professors at Graha Nusantara Padangsidimpuan University this study uses Mamdani fuzzy logic.